Emergence of NDM-5 Producing Carbapenem-Resistant Klebsiella aerogenes in a Pediatric Hospital in Shanghai, China - Fen Pan; Qi Xu; Hong Zhang (Frontiers Media S.A., 2021)
Background: Carbapenem-resistant Klebsiella aerogenes (CRKA) has posed a serious threat for clinical anti-infective therapy. However, the molecular characteristics of CRKA in Shanghai are rarely reported.Objective: This study aimed to investigate the resistance profiles, dissemination mechanism, and molecular characteristics of CRKA strains isolated from children in a pediatric hospital, Shanghai.Method: Fifty CRKA isolates were collected in 2019. Antimicrobial susceptibility of the strains was determined by broth microdilution method. The β-lactamases and outer membrane porin genes were characterized by polymerase chain reaction (PCR). Conjugation experiments were performed to determine the transferability of the plasmids. The plasmids were typed based on their incompatibility group using the PCR-based replicon typing method. Multilocus sequence typing (MLST) and enterobacterial repetitive intergenic consensus-PCR (ERIC-PCR) were performed for the genetic relationship.Results: All CRKA strains showed high level of resistance to cephalosporins and carbapenems, but still susceptible to aminoglycosides, colistin, and tigecycline. Forty five of fifty isolates carried blaNDM−5 genes (45/50, 90%), alongside with other β-Lactamase genes including blaCTX−M−1, blaTEM−1, and blaSHV−11 being detected. Loss of ompK35 and ompK36 genes were observed in 14% (7/50) and 28% (14/50), respectively, with 5 isolates lacking both ompK35 and ompK36. MLST analysis demonstrated that the majority of isolates belonged to ST4 (47/50, 94%) and ERIC-PCR fingerprinting was performed to identify NDM-5-producing isolates with approximately or more than 80% similarity levels. Plasmids carrying blaNDM−5 were successfully transferred to the E. coli recipient and plasmid typing showed that IncX3 were the prevalent among CRKA isolates.Conclusions: Our finding revealed the emergence of NDM-5 producing CRKA belonging to ST4 among children in Shanghai. Further attention should be paid to control the horizontal spread of the Class B carbapenemases like NDM in children.